FINTECH AS AN ENGINE TO A MORE INCLUSIVE FOOD SERVICE INDUSTRY IN QUEZON PROVINCE - Maguyon, Anna Peachy; Quendangan, Erwin (International Journal of Arts, Sciences and Education, 2025)
ABSTRACT The research aims to investigate the role of Financial Technology (Fintech) as an engine on the inclusion within food service industry in Quezon Province. Specifically, it study aims to determine the use of fintech product as to payment, digital banking, and financing; analyze the effect on level of financial inclusion as to connectivity, access, management, and transaction volume; identifying potential barriers and challenges hindering the widespread adaptation of fintech solution in business transaction; whether there is significant relationship in the usage of fintech product and impact factors on inclusion; and creating model of innovation. Descriptive method was used particularly quantitative research. The respondent are 210 willing owner/manager that are all user of fintech. The research include the towns and cities near the growth corridors of Quezon wherein there is concentration of business specified by the Department of Trade and Industry. Moreover, the data gathered are analyzed and interpret. The result reveals that in terms of usage, payment got the highest result. While in terms of financial inclusion, majority got the high result except management. It is identified that there is a lot of concern when it comes to security on financial data while using fintech platform. However, overall regression analysis confirms that the use of FinTech products has a significant positive effect on financial inclusion within the food service industry in Quezon Province. A model of innovation is developed based on the results. Keywords: access, connectivity, digital banking, financial inclusion, financing, fintech, management, payment, transaction volume